Hybrid Technique for Piezoelectric Operating Frequency Tuning - Shaheen, Murtadha; Mohammed Mlkat Al Mutoki, Sabah; M. Tufeik, Ishraq; Mossi, Karla; Ghanim Wadday, Ahmad (International Journal of Engineering and Technology, 2018)
The maximum electrical power is extracted from the piezoelectric generator when the resonance frequency matches that of the environmental vibration. To address this issue, mechanical or electrical tuning, and bandwidth widening strategies have been introduced. Mechanical tuning can be achieved by adjusting the mass or length of the structure. For electrical tuning, a shunt capacitor can be used to change the stiffness of a piezoelectric structure. The bandwidth widening can be accomplished by exploiting an array of structures each with a different resonant frequency. In this paper, a hybrid system using a multi piezoelectric bimorph cantilevers is deployed. This is based on achieving mechanical tuning, electrical tuning, and bandwidth widening simultaneously to develop a significant increment in piezoelectric frequency range. This method is performed by using three bimorph cantilevers. Each one has the same natural frequency, but using two different tip masses by mechanical tuning will result in three different natural frequencies. These cantilevers are connected in series to have a wide bandwidth energy harvester.Â